A systematic review of robotic colorectal surgery programs worldwide and a comprehensive description of local robotic training programme - Butnari, Valentin; Singh, Harpreet Kaur Sekhon Inderjit; Hamid, Eshtar; Hosny, Shady Gaafar; Kaul, Sandeep; Huang, Joseph; Boulton, Richard; Rajendran, Nirooshun (BMC medical education, 2025)
Background Robotic-assisted colorectal surgery (RACS) is gaining widespread adoption, with a growing number of procedures performed globally. These have been performed mostly by consultants, many of whom have gained sufficient proficiency to begin to educate their trainees. RACS offers a range of benefits to the surgeon and patient, yet safe and effective utilisation hinges on well-structured training programs for colorectal trainees within their general surgery residency. This systematic review aimed to evaluate the structure currently employed worldwide in RACS training programs for colorectal surgery trainees. In addition it delineates the conceptualization and implementation of a locally developed RACS program tailored to senior colorectal trainees and fellows at our Trust. Methods A comprehensive search of Ovid Medline and Embase databases (January 2010- March 2024) following PRISMA guidelines identified six studies reporting on RACS training curricula. Critical analysis of programme structure and curricula tools utilised was performed. Articles involving training of consultants were excluded. The quality and bias score of each study were assessed using the Newcastle Ottawa Score for observational studies. Results Six out of 77 studies were selected as suitable for analysis describing RACS training using Da Vinci platform. All apart from one programme described a phased or parallel robotic curriculum with four studies incorporating theoretical knowledge and laboratory or cadaveric training. Six programmes incorporated simulation, bedside assisting and console training. The use of validated objective or subjective metrics at each phase varied. Formal feedback is provided in only two of the programmes. Reflecting on above results we present our Trust training program which run over the last two years. Our program ensures clear learning goals for trainees and trainers, maintains patient safety, and is easily replicated across other UK RACS units. Conclusion The establishment of a standardised curriculum for colorectal surgery training worldwide, including in the UK, is vital. Currently, there is a scarcity of validated, objective assessment methods, which must be adequately standardised to create consistent progression criteria and competency-based metrics. Standardising these methods will enable reliable and robust assessment of trainee progression and competence to create a generation of robotically competent colorectal surgeons within their standard training program timeframe. PROSPERO database registration No.-CRD42024530340.